Truman - David McCullough (Simon and Schuster, 1992)
The story begins with Truman's origins in the raw, expansive world of the Missouri frontier. It chronicles a small-town, turn-of-the-century boyhood, family love, family trategy, and young Harry's years on the farm - years of relentless, often brutal work always cheerfully performed; of dogged learning; dogged courtship, optimism, in the face of defeat, and courage in the face of war in 1918, the experience that changed everything for Truman